ANALISIS KEUNTUNGAN USAHA PIA MELATI DI KELURAHAN MARIYAI KABUPATEN SORONG PAPUA BARAT - Doan Irando Fanindi; Mex Frans Lodwyk Sondakh; Yolanda Pinky Ivanna Rori (AGRI-SOSIOEKONOMI, 2018)
This study aims to calculate the business profit of "Pia Melati" in Mariyai Village, Sorong Regency, West Papua. This research was conducted for 3 months from September to November 2017. Data collection method used in this study is survey method. Data used is primary data by interviewingtechniques to business owners using a questionnaire. Secondary data was obtained from the Food and Industrial Processing Service of Sorong Regency. The results of this study indicate that this business costsfor a month is Rp.57,162,654, revenue is Rp.77,625,000 and profit is Rp.20,012,346. R/C ratio of 1.35, is indicated that this business is profitable.*llr+eprm*